2012
DOI: 10.1097/scs.0b013e318266fda3
|View full text |Cite
|
Sign up to set email alerts
|

Inferior Alveolar Nerve Injuries Associated With Mandibular Fractures

Abstract: The study evaluates the incidence of inferior alveolar nerve injuries in mandibular fractures, the duration of their recovery, and the factors associated with them. Fifty-two patients with mandibular fractures involving the ramus, angle, and body regions were included in this study; the inferior alveolar nerve was examined for neurological deficit posttraumatically using sharp/blunt differentiation method, and during the follow-up period the progression of neural recovery was assessed. The incidence of neural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 5 publications
3
30
0
Order By: Relevance
“…Almost one third of the study population showed postinjury preoperative mental nerve hypoesthesia and over 45% suffered from purely postoperative hypoesthesia without pre-existing posttraumatic nerve injury. This finding correlates with other studies that analysed the IAN function after mandibular fractures (Schultze-Mosgau et al, 1999;Halpern et al, 2004;Renzi et al, 2004;Bede et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Almost one third of the study population showed postinjury preoperative mental nerve hypoesthesia and over 45% suffered from purely postoperative hypoesthesia without pre-existing posttraumatic nerve injury. This finding correlates with other studies that analysed the IAN function after mandibular fractures (Schultze-Mosgau et al, 1999;Halpern et al, 2004;Renzi et al, 2004;Bede et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…However, literature shows several risk factors for IAN damage. Two studies, one performed by Bede et al, 2012, the other by Boffano et al, 2014, analysed that highly displaced fractures, such as comminuted fractures and fractures in close proximity to the inferior alveolar nerve (angle, ramus and body) are associated with higher posttraumatic inferior alveolar nerve injury rates. The present study supports similar results with worse recovery rates in patients with multiple fractures in the IAN area and especially high rates of hypoesthesia in mandibular angle fractures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study conducted by Bede et al [40], they found that linear displacement and comminuted fractures were which caused more nerve lesions and with a longer period of recovery. However recovery of nerve function in 91% of cases was obtained.…”
Section: Other Causes: Mandibular Fracturesmentioning
confidence: 99%